Current Perspectives in NSAID-Induced Gastropathy - Mau Sinha; Lovely Gautam; Prakash Kumar Shukla; Punit Kaur; Sujata Sharma; Tej P. Singh (Mediators of Inflammation)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are the most highly prescribed drugs in the world. Their analgesic, anti-inflammatory, and antipyretic actions may be beneficial; however, they are associated with severe side effects including gastrointestinal injury and peptic ulceration. Though several approaches for limiting these side effects have been adopted, like the use of COX-2 specific drugs, comedication of acid suppressants like proton pump inhibitors and prostaglandin analogs, these alternatives have limitations in terms of efficacy and side effects. In this paper, the mechanism of action of NSAIDs and their critical gastrointestinal complications have been reviewed. This paper also provides the information on different preventive measures prescribed to minimize such adverse effects and analyses the new suggested strategies for development of novel drugs to maintain the anti-inflammatory functions of NSAIDs along with effective gastrointestinal protection.